1988
DOI: 10.1111/j.1440-1746.1988.tb00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Auto‐immune hepatitis: Lifting the seventh veil

Abstract: Knowledge of auto‐immune chronic active hepatitis (AI‐CAH) has developed since the 1940s. Using the analogy of the seven veils, the lifting of the first six could be represented by the finding of: hypergammaglobulinaemia; recognition of the clinical syndrome; the hepatic histopathology; the auto‐immune serological markers; the response to corticosteroid/immuno‐suppressive drugs; and the immunogenetic association with HLA B8; DR3. The lifting of the seventh veil, the ultimate understanding of AI‐CAH, will requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Patients were recruited into this study between January 1986 and August 1994. All cases were required to satisfy previous criteria for the diagnosis of autoimmune hepatitis, 10 and subsequent review has confirmed that all cases also conform to a ‘definite’ or ‘probable’ diagnosis of autoimmune hepatitis according to the criteria of the International Autoimmune Hepatitis Group 11 . The study conformed to current international guidelines for human experimentation, was approved by the Human Ethics Committee of the Western Sydney Area Health Service, and all subjects gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were recruited into this study between January 1986 and August 1994. All cases were required to satisfy previous criteria for the diagnosis of autoimmune hepatitis, 10 and subsequent review has confirmed that all cases also conform to a ‘definite’ or ‘probable’ diagnosis of autoimmune hepatitis according to the criteria of the International Autoimmune Hepatitis Group 11 . The study conformed to current international guidelines for human experimentation, was approved by the Human Ethics Committee of the Western Sydney Area Health Service, and all subjects gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Diagnosis of autoimmune liver disease is often difficult and should be based on clinical findings and the presence of autoantibodies in the serum (20). To determine whether our patients with cryptogenic cirrhosis had a previously unrecognized form of autoimmune liver disease, we (a) reevaluated clinical findings typically associated with autoimmune disease by forming an autoimmune score from five clinical criteria typically found in autoimmune liver disease and (b) tested sera of patients with cryptogenic cirrhosis for the presence of various autoantibodies.…”
Section: Many Of the Patients Referred With Blood-borne Nanbmentioning
confidence: 99%